- Sosialisasi Peningkatan Kesadaran dan Keselamatan Berkendara di Kalangan Remaja SMA Negeri 2 Kelurahan Waru, Penajam Paser Utara - Matyani Matyani; Orland Diadema Garibaldi Sofyan; Nurini Aprilia Wati; Vinny Cahya Wulan Putri; Khezya Cartila Jhodelyn; Nurmila Chayrunisa; Wahyu Nurhasan; Nursella Nursella; Rhendy Anindra; Muhammad Fatahila Alfaridzi; Nur Hadayati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
Driving safety is a pressing issue around the world, with traffic accidents continuing to pose a threat to society. Factors such as an increase in the number of vehicles, lack of awareness of traffic rules, as well as a lack of safe infrastructure have led to a high number of accidents and fatalities. This study investigates various aspects of driving safety, including the role of technology in reducing the risk of accidents, education on traffic awareness, and the role of government in providing safe infrastructure. The purpose of this community service is to increase knowledge and the importance of awareness about driving safety in SMA Negeri 2 Penajam Paser Utara students. The implementation method used is in the form of teaching and interactive discussions about the importance of safe driving for students. The result of the research conducted is the realization of increased awareness and safety driving for teenagers of SMA Negeri 2 Penajam Paser Utara students. It is recommended that the government and related parties provide more socialization and education to students and the community regarding driving safety. For motorists, it is recommended to keep driving safely and be disciplined in obeying traffic regulations.